How cognitive proximity enables an entrepreneurial ecosystem with limited resources to support biopharma SMEs - Gonzalez Lopez, Jose Francisco (2022)
This thesis employs cognitive proximity as a theoretical lens to understand how an entrepreneurial ecosystem in a second-tier region supports biopharma SMEs whilst being constrained by limited access to funding and a lack of sustained sector-specific support from the government. Cognitive proximity is chosen to address the research question “how does a second-tier region support SME activity in the biopharma industry?” as it considers the importance of common languages, similar knowledge bases, and shared goals to facilitate interactions between organisations in an entrepreneurial ecosystem.